2008
DOI: 10.1093/humrep/den217
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic screening in women of advanced maternal age caused a decrease in clinical pregnancy rate: a randomized controlled trial

Abstract: ISRCTN38014610.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(162 citation statements)
references
References 31 publications
6
148
1
7
Order By: Relevance
“…Thus, downstream developmental processes can be irreparably compromised by removing a cell from the embryo. Such an impact is also reflected in a lower blastocyst rate after cleavage-stage biopsy with respect to undisturbed embryos, as reported in several papers [32][33][34].…”
Section: Discussionmentioning
confidence: 71%
“…Thus, downstream developmental processes can be irreparably compromised by removing a cell from the embryo. Such an impact is also reflected in a lower blastocyst rate after cleavage-stage biopsy with respect to undisturbed embryos, as reported in several papers [32][33][34].…”
Section: Discussionmentioning
confidence: 71%
“…It took above noted Dutch study [2] to stop to a degree this worldwide utilization of PGS. Other studies later reaffirmed the results reported by Mastenbroek et al [3][4][5][6]. Professional organizations followed by unequivocally concluding that PGS, at current practice levels, did not improve clinical IVF outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 72%
“…The failure of PGS#1, however, refuted their prediction in its universality. As noted before, studies demonstrated not only lack of efficacy in improving IVF outcomes but, actually, decreased pregnancy chances as consequence of PGS in older women [1][2][3]. The theoretical concept that pretransfer elimination of aneuploid embryos should improve IVF outcomes has, however, nevertheless survived, though remains in search of a suitable patient population where PGS can, indeed, be unequivocally demonstrated to be effective in improving IVF outcomes.…”
Section: Search Strategymentioning
confidence: 95%
See 1 more Smart Citation
“…93% of trisomy 18, 95% of trisomy 21 and 100% of trisomy 16. Advanced maternal age is the major risk factor for oocyte aneuploidy, mainly due to premature separation of sister chromatids [4,5].…”
Section: Introductionmentioning
confidence: 99%